Structural elucidation of irish organic farmed salmon (salmo salar) polar lipids with antithrombotic activities - Tsoupras, Alexandros; Lordan, Ronan; Demuru, Martina; Shiels, Katie; Kumar Saha, Sushanta; Nasopoulou, Constantina; Zabetakis, Ioannis (MDPI, 2018)
peer-reviewed While several marine polar lipids (PL) have exhibited cardioprotective properties through their effects on the platelet-activating factor (PAF) pathways, salmon PL have not been tested so far. In this study, the antithrombotic activities of salmon PL were assessed in human platelets and the structural characterisation of bioactive salmon PL was performed by GC-MS and LC-MS analyses. PL from fillets of Irish organic farmed salmon (Salmo salar) were extracted and separated into several lipid subclasses by thin-layer chromatography (TLC), while their fatty acid profile was fully characterised by GC-MS. Salmon total lipids (TL), total neutral lipids (TNL), total polar lipids (TPL), and each PL subclass obtained by TLC were further assessed for their in vitro effects towards PAF-induced and thrombin-induced platelet aggregation in human platelets. Salmon PL exhibited antithrombotic effects on human platelet aggregation, mostly through their strong inhibitory effects against the PAF pathway with IC50 values comparable to other marine PL, but with lower effects towards the thrombin pathway. PL fractions corresponding to phosphatidylcholine and phosphatidylethanolamine derivatives exhibited the most potent anti-PAF effects, while LC-MS analysis putatively elucidated their structure/function relationship. Several diacyl-PC/PE and alkyl-acyl-PC/PE species containing mostly docosahexaenoic acid at their sn-2 glycerol-backbone may be responsible for the bioactivity. The data presented suggests that salmon contains PL with strong antithrombotic bioactivities.